2003
DOI: 10.1021/np0202428
|View full text |Cite
|
Sign up to set email alerts
|

New Dihydroalkylhexenones from Lannea edulis

Abstract: Activity-guided isolation of radical-scavenging compounds from the dichloromethane extract of the root bark of Lannea edulis led to isolation of two known bioactive alkylphenols [cardonol 7 (1) and cardonol 13 (2)], and three new dihydroalkylhexenones were also isolated (3-5). Their structures were elucidated by spectroscopic and chemical methods. The absolute configuration of 4 was determined by the Mosher ester method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 8 publications
(26 reference statements)
1
28
0
2
Order By: Relevance
“…These compounds, named as phenolic lipids, show nematicidal (Velászquez et al, 2003), antioxidant (Valcic et al, 2002), antifungical, and cytotoxic activities (Queiroz et al, 2003;Davis et al, 1997;Correia et al, 2001).…”
Section: In Vitro Cytotoxic Activity Of Brazilian Middle West Plant Ementioning
confidence: 99%
“…These compounds, named as phenolic lipids, show nematicidal (Velászquez et al, 2003), antioxidant (Valcic et al, 2002), antifungical, and cytotoxic activities (Queiroz et al, 2003;Davis et al, 1997;Correia et al, 2001).…”
Section: In Vitro Cytotoxic Activity Of Brazilian Middle West Plant Ementioning
confidence: 99%
“…Lithraea molleoides 78,79 Lithraea caustica 70 73 Campnosperma auriculata 4 Lannea edulis 77 Lannea edulis 77 24 bilidade das porções fenólicas nas regiões lipídicas, nas quais é requerida proteção contra degradação biológica ou oxidação quí-mica. A influência da cadeia alquílica no mecanismo de proteção é similar ao efeito que é proposto para a cadeia poliprenílica do tocoferol 75 .…”
Section: Tabela 3 Lipídios Fenólicos E Derivados Isolados De Espécieunclassified
“…O isolamento dessas substâncias é mais um dado que corrobora a proposta biossintética de Walters e colaboradores 87 . Estes derivados alquilados da ciclo-hexanona também já foram relatados em duas espécies do gênero Lannea, L. welwitschii e L. edulis 73,77 (Tabela 3) . .…”
Section: Lipídios Fenólicos Não Usuais Na Família Anacardiaceaeunclassified
“…Phytochemical studies of other Lannea species also reported the presence of flavonoids, tannins, alkaloids, saponins and phenols [22][23][24]. [26], antiulcer properties [27], antioxidant [28] and antiinflammatory activities [29].…”
Section: Resultsmentioning
confidence: 99%